A Holistic Approach for Low Cost Heliostat Fields. (May 2015) - Pfahl, A.; Randt, M.; Meier, F.; Zaschke, M.; Geurts, C.P.W.; Buselmeier, M.
Abstract: The AutoR-project takes a holistic approach to reduce the cost of heliostat fields: Wireless control and energy supply enables to use smaller heliostats which need less steel per mirror area (but usually have high wiring cost). A low cost but high efficient drive system is chosen which reduces energy consumption to a minimum amount and leads to low cost for PV cell and energy storage. The usual boundary layer wind tunnels tests for heliostats are proven regarding energy spectra to avoid oversizing of steel structure and drives or failures because of underestimations of the loads. The concepts for wireless control and energy supply, the wind tunnel investigations and the first rim drive heliostat prototype are presented.